Qualitative study of quality awareness and enhancement through interactive training tool - Weili, Siong. (UNIMAS, 2006)
Quality control is very important in today manufacturing industry. This is because many advantages can be obtained when quality control is implemented properly. Those company that implementing quality control in their production for instant, will gain a higher benefit.This shows that education or training program about quality control is very important.The problem faced is lack of appropriate tool for learning and training about quality control. Most of the training and learning process still using traditional method which is using text book.Based on the fact above, an interactive training tool was developed. This interactive tool will teach the user how to construct control chart.Control chart was selected because of its ability to determine the process capability and for on-line control. Besides that i tcan also be used for both variable and attribute values.To test the effectiveness of the interactive tool, a usability test was conducted where 10 participants were selected. The main usability characteristics that had been look into are the technical and subjective characteristic. Based on the result of the evaluation, the author found out that some improvements need to be done. The causes of the problems were because of lack of experience in developing computer interface.